Sensors-Based Electric Machine Design for Industry - Shaikh Heena T; Dr. Kazi Kutubuddin Sayyad Liyakat (International Journal of Electrical Machine Analysis and Design, 2026)
The integration of advanced sensors is fundamentally changing the economics and reliability of electric machines. It moves design focus from minimizing material cost and adhering to conservative standards toward maximizing operational availability and energy efficiency. In the industry of tomorrow, the electric motor will not be a passive collection of coils and steel, but a self-diagnosing, self-optimizing, and perhaps even self-healing asset—a sentient motor—driven by its highly refined sixth sense, ensuring that the wheels of industry turn with unparalleled precision and resilience. The relentless drive for efficiency, reliability, and intelligence in modern industrial operations necessitates a paradigm shift in electric machine design. This abstract introduces the transformative concept of sensors-based electric machine design, wherein sensing capabilities are not merely added as afterthoughts but are intrinsically integrated into the foundational architecture of motors, generators, and actuators from the conceptual stage. This approach moves beyond traditional control loops, fostering machines that are "self-aware." By embedding a diverse array of sensors—measuring parameters like speed, torque, temperature, vibration, current, voltage, and magnetic flux—designers can create systems that offer unparalleled precision control, real-time diagnostics, and predictive maintenance capabilities. This integration enables sophisticated closed-loop control algorithms, facilitates digital twin creation for virtual commissioning and lifecycle management, and lays the groundwork for truly autonomous and self-optimizing industrial electromechanical systems. Ultimately, sensors-based design is key to unlocking new levels of performance, energy optimization, and operational longevity, positioning industry for the demands of Industry 4.0 and beyond.
Keywords: Electric Machine; Industry 4.0; Speed; electric motor; sensor; torque